Risk of Neurologic Sequelae with Bacterial Meningitis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2002)
Predictors of permanent neurologic sequelae or death following bacterial meningitis were determined in a case-controlled study at Sophia Children's Hospital, Rotterdam, The Netherlands.